THE ROLE AND IMPORTANCE OF TOURISM INFRASTRUCTURE IN THE DEVELOPMENT OF REGIONAL TOURISM - Mirza Qilichbayevich Sabirov (International Journal of Economic Integration and Regional Competitiveness, 2024)
This article focuses on the challenges of developing regional tourism infrastructure. The article also defines the essence of the concept of "regional tourism infrastructure" and its importance in the development of the region, its content and development problems. Based on the studied materials, conclusions and practical recommendations are given for improving tourism infrastructure in the region.